1999
DOI: 10.4269/ajtmh.1999.60.793
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for infection with Toxoplasma gondii for residents and workers on swine farms in Illinois.

Abstract: Abstract. Risk factors for Toxoplasma gondii infection in workers and residents of swine farms were studied on 43 farms in Illinois. Blood samples were collected from 174 adults in 1993. The T. gondii seroprevalence was 31%. An interview was conducted with each participant, obtaining information on demographic characteristics and behaviors suspected to affect the risk of T. gondii infection. Factors associated with increased risk of T. gondii seropositivity were a higher number of seropositive cats trapped on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 44 publications
0
44
0
2
Order By: Relevance
“…It is likely that workers that have handled infected animals were carrying the parasite from their contaminated hands to their mouths. In a study of 174 workers and residents of swine workers in the USA, Weigel and coworkers [12] attributed an increased risk of T. gondii seropositivity in males to less attention paid to cleanliness in food preparation and eating. Workers in contact with animals might be more frequently in contact with T. gondii than subjects without contact with animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that workers that have handled infected animals were carrying the parasite from their contaminated hands to their mouths. In a study of 174 workers and residents of swine workers in the USA, Weigel and coworkers [12] attributed an increased risk of T. gondii seropositivity in males to less attention paid to cleanliness in food preparation and eating. Workers in contact with animals might be more frequently in contact with T. gondii than subjects without contact with animals.…”
Section: Discussionmentioning
confidence: 99%
“…Only few descriptive studies about the seroprevalence of T. gondii infection in people occupationally exposed to animals including veterinarians [10,11] and farmers [12] have been reported. However, to the best of our knowledge, there is no any case-control study that had determined the association between T. gondii infection and occupational exposure to live animals.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth stating that the increase in the risk of seropositivity in men found in a 134-person's prevalence study was explained by the authors as caused by carelessness at the time of cleaning and food preparation 17 .…”
Section: Socio-demographic Risk Factorsmentioning
confidence: 98%
“…(24 vs. 11%, respectively, p = 0.01) 30 . A study in Illinois, USA, also reported an association between cats infected with T. gondii and an increased risk of human infections due to soil contact as a probable mechanism of transmission 17 . In contrast, the European multicentric study of risk factors did not find a strong association between having cat and T. gondii infection 31 .…”
Section: Risk Factors Linked To Lifestylementioning
confidence: 99%
“…There was not significant relation between pregnant women who worked in the garden around their houses with toxoplasmosis infection incidents (p=0.29 > 0.05). Weigel et al (1999) 16 found different result in Europe, almost 17% pregnant women infected by toxoplasmosis because of contacts with soil. Similar result also found by Spalding et al (2005) 17 who stated that contacts with soil were high risk factor of toxoplasmosis infection for pregnant women.…”
mentioning
confidence: 98%